DEDIKASI ULAMA KALIMANTAN DALAM MENGATASI POLEMIK PANDEMI COVID-19 - M. Miftah Arief; Noor Azmi (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Ulama are community leaders who have the highest religious competence in society and lead Ulama to become religious leaders. In addition to religious leadership, ulama also have social leadership that is able to control many individuals or groups. This study aims to reveal the form of clerical leadership in South Kalimantan during the Covid-19 condition. This study uses a qualitative approach with descriptive analysis. The research data is taken from some information posted on trusted websites. The results of the study show that ulama in South Kalimantan practice religious transformational leadership in society.